O exercício profissional das assistentes sociais no Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso : demandas sociais e respostas profissionais - Ferreira, Soraide Isabel (2019)
This dissertation aims to analyze the professional practice of Social Assistants who work within the scope of the Federal Institute of Education, Science and Technology of Mato Grosso (IFMT), based on social demands and professional responses. For this, we are guided by the premises of Guerra (2012), Santos (2013) and Torres (2017), which define professional practice as a synthesis of “multiple determinations”, which requires undertaking the debate from a historical-critical perspective, considering the conjunctural and institutional conditions that surround professional practice in this space. This relationship gives the professional practice an ethical-political commitment in the form of intervening in the expressions of the social issue that are expressed in the daily work of the IFMT, as well as a deeper analysis of reality, surrounded by factors that impact the development of professional actions . To achieve the objective, we used descriptive research, of a qualitative nature and as a data collection technique, semi- structured interviews were used with 9 (nine) Social Workers from different campuses in the state of Mato Grosso. The results of the research showed that the professional practice of IFMT Social Workers is impacted by conditions and work relations, resulting from the neoliberal offensive and the consequent counter-reform of Education, which ends up imposing limits on professional practice, in the face of increased demands required in a bureaucratic and emergency manner. It also reiterates the difficulty of multiprofessional work due to issues that involve the composition of a student service team that is still incomplete and work overload. Issues such as hierarchy and power relationship appear as factors that hinder the relative autonomy of professionals. With regard to the growing number of institutional requests, demands from the profession itself, from students and the family, we found that they hamper the process of planning and systematizing actions, which interferes in the development and development of professional strategies. In addition, we show that the process of resolving demands is addressed individually, urgently and immediately. These findings point to the need for permanent investment in Professional and Technological Education; hiring more professionals from the Social Service area; strengthening intersectoriality; the development of socio-educational actions and the continuous holding of the IFMT Student Assistance Forum.